Application of nuclear medicine techniques in sports medicine - Patrycja Zuziak; Natalia Ilnicka; Daria Matyja; Maria Sadlik; Leila Abod (Kazimierz Wielki University, 2023)
Introduction and purpose: To briefly introduce the reader to the application of nuclear medicine studies in the diagnosis and treatment of musculoskeletal disorders developed among athletes.    Materials and methods: To prepare this review, publications indexed in the PubMed and Google Scholar databases were analyzed. Special attention was given to full-text articles published in English between 2015 and 2023, as well as to the references cited by the authors of selected publications. Description of the state of knowledge: Nuclear medicine is applied in the diagnosis and therapy of orthopedic conditions. Commonly used nuclear medicine techniques include planar bone scintigraphy (WBS), single-photon emission computed tomography (SPECT) combined with computed tomography (CT), and positron emission tomography (PET) combined with computed tomography (CT). Summary: The utilization of nuclear medicine techniques allows for proper diagnosis and early treatment of musculoskeletal disorders, including pathologies resulting from sports-related physical activity.